A broad class of zero‐or‐one inflated regression models for rates and proportions. Issue 2 (22nd October 2020) - Queiroz, Francisco F.; Lemonte, Artur J.
Abstract: We introduce a family of distributions with bounded support for continuous rates or proportions when the data contain zeros or ones. On the basis of this class of distributions, we propose a novel class of regression models which is useful for modelling fractional data observed on [0,  1) or (0,  1]. The response variable of the new class of regression models has a mixed continuous‐discrete distribution with probability mass at zero or one, and the parameters of the mixture distribution are modelled through regression structures involving covariates and unknown parameters. An advantage of this class of regression models is the ability to deal with atypical observations. We consider a frequentist approach to performing inferences, and the traditional maximum likelihood method is employed to estimate the regression parameters. We also propose a residual analysis for the novel class of regression models to assess departures from model assumptions. Additionally, global and local influence methods are discussed. An empirical application that employs real data is considered to illustrate the usefulness of the new class of regression models in practice. Résumé: Les auteurs présentent une famille de distributions à support borné pour des taux ou des proportions continus lorsque les données comportent des zéros et des uns. Sur la base de cette classe de distributions, ils proposent une nouvelle classe de modèles de régression s'avérant utiles pour modéliser des données fractionnelles observées sur les intervalles [0,  1) ou (0,  1]. La variable réponse de la nouvelle classe de modèles de régression possède une distribution mixte continue et discrète avec une masse à zéro ou un. Les paramètres du mélange sont modélisés à travers des structures de régression comportant des covariables et des paramètres inconnus, ce qui lui confère l'avantage de pouvoir gérer des observations atypiques. Les auteurs présentent une approche fréquentiste pour l'inférence en employant la traditionnelle méthode du maximum de vraisemblance pour estimer les paramètres de régression. Ils proposent également une analyse des résidus de cette nouvelle classe de modèles afin d'évaluer le respect des hypothèses du modèle, puis discutent de méthodes pour mesurer l'influence locale et globale. Les auteurs illustrent l'utilité de leur nouvelle classe de modèles de régression par l'analyse de données réelles.